Correlation between longitudinal serum vitamin D levels and myopia in children: a prospective birth cohort analysis - Ju-Hsien Li; Ho-Min Chen; Kuan-Wen Su; Yu-Kai Kuo; Cheng-Hsiu Wu; Nan-Ni Chen; Pei-Wei Huang; Chi-Chin Sun (BMC Ophthalmology)
Abstract Background Myopia is an increasingly prevalent visual impairment associated with severe ocular complications. Risk factors for childhood myopia include genetics, East Asian ethnicity, age, parental myopia, and various environmental factors. The relationship between vitamin D levels, outdoor activity, and myopia remains inconclusive. This study aims to investigate the correlation between longitudinal serum vitamin D levels and myopia in Taiwanese children. Methods The study measured serum 25-hydroxyvitamin D (25(OH)D) concentrations in children from the Prediction of Allergies in Taiwanese Children (PATCH) study at multiple time points, including umbilical cord blood and ages 1, 3, and 5 years. Refractive error under cycloplegic conditions and axial length were assessed from January 2021 to April 2022. Myopia was defined as a mean spherical equivalent in both eyes ≤ -0.5 diopter. Independent sample t-tests, partial correlation analyses, and generalized estimating equation (GEE) analyses were conducted to examine the relationship between serum vitamin D concentrations and myopia. Results A total of 126 eyes from 63 children (mean age: 8.90 ± 2.24 years) were analyzed. The lowest serum vitamin D level (19.11 ± 9.10 ng/mL) was observed in umbilical cord blood, while the highest level (37.01 ± 12.61 ng/mL) occurred at 1 year of age. No significant differences in serum vitamin D concentrations were found between children with and without myopia during gestation, at birth, or at ages 1, 3, and 5 years (all P > 0.05). Additionally, GEE analysis revealed that serum vitamin D levels were not significantly associated with cycloplegic spherical equivalent or axial length after adjusting for age and sex. Conclusions This prospective birth cohort study found no association between serum vitamin D concentrations at birth, 1, 3, or 5 years of age and the development of myopia in Taiwanese children. These findings suggest that other factors, such as ethnicity, near work activities, or lighting conditions, may play more significant roles in myopia development, particularly among East Asian populations.